2023
DOI: 10.1126/science.abj7412
|View full text |Cite
|
Sign up to set email alerts
|

BTG1 mutation yields supercompetitive B cells primed for malignant transformation

Abstract: Multicellular life requires altruistic cooperation between cells. The adaptive immune system is a notable exception, wherein germinal center B cells compete vigorously for limiting positive selection signals. Studying primary human lymphomas and developing new mouse models, we found that mutations affecting BTG1 disrupt a critical immune gatekeeper mechanism that strictly limits B cell fitness during antibody affinity maturation. This mechanism converted germinal center B cells into sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 111 publications
0
23
0
Order By: Relevance
“…47 Inactivating BTG1 mutations promote lymphomagenesis by dysregulating several key processes leading to enhanced oncogenic fitness and cell migration. 48,49 The mutations we identified in CARD11 were located within the coiled-coil domain of scaffold protein CARD11 (K215Q and L341V), a region that is often mutated in DLBCL. 50 CARD11 is a crucial adaptor protein acting downstream of antigen receptor signaling, regulating signaling pathways involved in immune function and cell survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Inactivating BTG1 mutations promote lymphomagenesis by dysregulating several key processes leading to enhanced oncogenic fitness and cell migration. 48,49 The mutations we identified in CARD11 were located within the coiled-coil domain of scaffold protein CARD11 (K215Q and L341V), a region that is often mutated in DLBCL. 50 CARD11 is a crucial adaptor protein acting downstream of antigen receptor signaling, regulating signaling pathways involved in immune function and cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Antiproliferation proteins BTG1 and BTG2 represent 2 functionally related tumor suppressors of the BTG/TOB protein family that play a role in multiple cellular processes, including transcription regulation, DNA repair, cell division, and messenger RNA stability 47 . Inactivating BTG1 mutations promote lymphomagenesis by dysregulating several key processes leading to enhanced oncogenic fitness and cell migration 48 , 49 . The mutations we identified in CARD11 were located within the coiled‐coil domain of scaffold protein CARD11 (K215Q and L341V), a region that is often mutated in DLBCL 50 .…”
Section: Discussionmentioning
confidence: 99%
“…No reports have examined the function of BTG2 in malignant lymphoma pathogenesis, although BTG2 mutations are frequently found in several lymphomas, such as DLBCL 46 and FL, 47 and this mutation was reported as a poor prognostic factor in primary testicular DLBCL 48 . Recently, some studies have demonstrated that functional disruption of BTG1, which belongs to the APRO family and is frequently mutated in GCB‐DLBCL and FL, drives the formation of aggressive BCLs 49,50 . BTG1 acts as an immune gatekeeper in GC B cells and mutant BTG1 promotes aggressive BCLs in humans and mice 49 .…”
Section: Discussionmentioning
confidence: 99%
“…is frequently mutated in GCB-DLBCL and FL, drives the formation of aggressive BCLs. 49,50 BTG1 acts as an immune gatekeeper in GC…”
Section: Ack N Owled G M Entsmentioning
confidence: 99%
“…The number of samples with mutation at each amino acid position, regardless of the change (missense, nonsense, insertion or deletion) are reported. For the DLBCL mutation hotspot analysis, the data from the FishHook analysis by Mlynarczyk et al were downloaded 34 . This analysis was performed with a cohort of 101 DLBCL cases from the ICGC/TCGA Pan-Cancer Analysis of Whole Genomes Consortium 35 .…”
Section: Cancer Mutation Analysismentioning
confidence: 99%